Consciência social e pesquisa científica: uma análise sobre a experiência de professores do Ensino Superior brasileiro - Rosa, Fabiane Ramos (2023)
This research investigates the types of Social Consciousness of professors who work in Higher Education Institutions and their relationship with the development of scientific research, adopting the Conceptual Model on Political Consciousness as a reference for the development of the concept of Social Consciousness. In a context of crisis in the science areas, the emigration of researchers and the need for articulation between Higher Education Institutions (HEIs), this thesis aims to identify different configurations of Social Consciousness among professors who develop scientific research considering the dimensions of analysis of Consciousness, and how professors respond to social transformations. The data indicated different configurations of Social Consciousness, called in this thesis Social Consciousness of Helplessness, Development, Solitude and Attachment. Social Consciousness refers to the individual who reflects on his own reality and, through restlessness and questioning, acts on it responding to social transformations in a movement that characterizes scientific practice